Japan in the Indian Ocean: An integral and holistic involvement in South Asia. (2nd January 2020) - Maniyar, Jay
ABSTRACT: Japan has had and continues to have a diverse set of interests pertaining to South Asia and the vast expanse of the Indian Ocean Region. The article below assesses the emerging maritime interests of Japan in the Indian Ocean and aspects of maritime security, maritime cooperation, infrastructure investments, food security, etc. and attempts to devise an approach for Japan in the twenty-first century security scenarios of the world's third largest ocean. The Indian Ocean is responsible for the passage of Japan's imports of oil, 90 percent of which are sourced from the oil-rich region of the Arabian Gulf. While the criticality of the Indian Ocean in terms of security threats such as piracy and armed robbery remains considerably behind the Pacific Ocean's and other critical sea bodies such as the South and East China Seas, a strategy for India, the Indian Ocean, and South Asia befits the drawing up of avant-garde strategies, doctrines, operational and tactical prowess.